Enhanced resistance to He ions irradiation damage of nanocrystalline SiC coating - Qiqi Li; Yulin Wei; Xiangbin Ding; Yantao Gao; Min Liu (Journal of Advanced Ceramics, 2025)
This study focuses on the resistance of nanocrystalline SiC coatings in reactors to He ion irradiation damage, revealing the crucial role of grain boundaries. In the nanocrystalline SiC coating, high-density grain boundaries (GBs) and stacking faults (SFs) formed a GB–SF network. This network preferentially captured He atoms and inhibited the nucleation and growth of He bubbles and dislocations within the lattice. Moreover, the decrease in He atoms within the lattice accelerated the recombination of lattice defects. Although the abundant grain boundaries lead to extensive nucleation of dislocations, they restrict the growth of dislocations. Eventually, large He bubbles, continuous gas-filled disc (CGD)-type platelets, and black spots formed at the grain boundaries. Compared with traditional coarse-crystalline chemical vapor deposition (CVD)-SiC, this unique defect structure remarkably reduced the hindrance to dislocation movement and enhanced the resistance of the coating to irradiation hardening. This provides a key reference for the research on optimizing the in-reactor service performance of SiC through grain-boundary regulation strategies.